The Analysis Study of Risk Factor and Management for Severe Perineal Lacerations during Childbirth: A Comprehensive Systematic Review - Ristiana, Ria; Bakhtiar, Bustaman; Halim, Haerianty (International Medical Journal Corp. Ltd, 2024)
Background: The aim of this study to show about risk factor and management for severe perineal lacerations during childbirth. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Various independent risk factors have been recognized to be associated with these severe perineal lacerations. Increased maternal age, nulliparity, induction of labor, epidural analgesia, prolonged duration of second stage of labor, fetal macrosomia, persistent occipitoposterior position and instrumental delivery are the most frequently reported. Suture repair is relatively contraindicated for hemostatic perineal lacerations. Conservative management is preferred for hemostatic lacerations. For lacerations with persistent bleeding or anatomical distortion requiring repair, treatment should be delayed if an appropriately trained clinician is unavailable.